Efektifitas Pendekatan Matematika Realistik terhadap Keterampilan Berpikir Kritis Siswa SD - Magdalena, Ina; Kurniawan, Irwan; Pratiwi, Annisa Dwi; Fitriah, Hasanah; Firlyansyah, Hilda; Yuliyani, Tika (ANWARUL, 2022)
This study aims to analyze the effectiveness of using a realistic mathematical approach to improve critical thinking skills in fourth grade elementary school students at SDN Perumnas 9 Tangerang. The method used is experimentation by giving an initial test in the form of story questions that provoke students to think about solving these questions. After the results were obtained on the initial test, a realistic mathematics approach was carried out with two lessons. After that, a final test was carried out to test the effectiveness of a realistic mathematical approach in learning. Based on the results of the analysis, it can be described as an increase in the critical thinking skills of elementary school students after being taught using a realistic approach. Students can connect formulas, numbers in mathematics to solve everyday problems. In addition, students are more enthusiastic and motivated to solve the problem.